Centaurea susannae (Cardueae, Compositae): A new species from protected coastal areas in Portugal - Invernón, Vanessa R.; Devesa, Juan Antonio; López, Eusebio (Phytotaxa, 2012)
Centaurea susannae, a new species from Portugal, is described and illustrated. It belongs to sect. Seridia and strongly resembles C. lusitanica and C. sphaerocephala with both of which it has been confused. It differs from the former in its sessile, auriculate, cauline leaves and its smaller size, and from the latter in its pappose achenes and in shorter spines at the appendage of the middle involucral bracts, usually less than 5 mm long. The present study also reports the chromosome number for this species, i.e. 2n = 22. Centaurea susannae is limited to a few populations in two small regions of the Portuguese coast which lie within protected areas.